FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN ALAT KONTRASEPSI - Dita Wasthu Prasida (Jurnal Ilmiah Global Education, 2023)
Family Planning (KB) is a program established by the National Population and Family Planning Agency (BKKBN) which aims to control the population in Indonesia. In implementing the family planning program, this is done by using contraceptives. The word contraception comes from the word "contra" which means to prevent and "conception" which means a meeting between a sperm cell and a mature egg cell which results in fertilization. According to Law No. 52 of 2009 regulates Population Development and Family Development. The manifestation of this program is the creation of regular pregnancies, determining the right age for giving birth, and maintaining one's reproductive rights (Ministry of Health RI, 2015). This population control is carried out in an effort to minimize population density and improve the quality of Human Resources (HR) in Indonesia. The research method used in this study is a literature review by analyzing journals about the factors that influence contraceptive devices from Google Schoolar between 2023. The results of the study using a literature review obtained that from the 8 journals analyzed it was found that many factors influenced the choice of device. contraception. The results of the research analyzed by the researcher, from eight (8) journals showed that in five (5) journals that husband's support was the main factor influencing the choice of contraceptives. While other factors that influence the choice of contraceptives are age, education, level of knowledge, parity, income, employment and support from health workers.